Upper bounds of the risk of nearest neighbor rules for finite samples - Rizk, Mohamed (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, based on the integral expressions for the conditional risk and the risk ,we evaluate the upper bounds of the risk for some important distributions with unbounded support